Study of the buckling effects on the electrical and optical properties of the group III-Nitride monolayers. (1st November 2022) - Abdullah, Nzar Rauf; Abdullah, Botan Jawdat; Rashid, Hunar Omar; Tang, Chi-Shung; Gudmundsson, Vidar
Abstract: We consider electronic and optical properties of group III-Nitride monolayers using first-principle calculations. The group III-Nitride monolayers have flat hexagonal structures with almost zero planar buckling, Δ . By tuning the Δ, the strong σ - σ bond through sp 2 hybridization of a flat form of these monolayers can be changed to a stronger σ - π bond through sp 3 hybridization. Consequently, the band gaps of the monolayers are tuned due to a dislocation of the s - and p -orbitals towards the Fermi energy. The band gaps decrease with increasing Δ for those flat monolayers, which have a band gap greater than 1 . 0 eV, while no noticeable change or a flat dispersion of the band gap is seen for the flat monolayers, that have a band gap less than 1 . 0 eV . The decreased band gap causes a decrease in the excitation energy, and thus the static dielectric function, refractive index, and the optical conductivity are increased. In contrast, the flat band gap dispersion of few monolayers in the group III-Nitride induces a reduction in the static dielectric function, the refractive index, and the optical conductivity. We therefore confirm that tuning of the planar buckling can be used to control the physical properties of these monolayers, both for an enhancement and a reduction of the optical properties. These results are of interest for the design of optoelectric devices in nanoscale systems.